The Short-Run and Long-Run Dynamics between Foreign Direct Investment and Economic Growth: A Case of Sri Lanka - Tharsika, K.; Litharsini, K.; Pratheepkanth, P. (4 th Research Conference on Business Studies (RCBS) - 2022 (p. 10).UNiversity of Vavuniya., 2022)
Foreign Direct Investment (FDI) has long been regarded as one of the most critical factors influencing economic growth. Previous empirical research on the relationship between FDI and economic growth yielded inconclusive results. The growth rate of Sri Lanka’s Gross Domestic Product (GDP) had slowed in recent years, particularly in 2020, when it was negative. Meanwhile, the Sri Lankan government has been working on several initiatives, including the Colombo International Financial City, to increase future FDI. As a result, this research aims to investigate the short- and long-term relationship between FDI and economic growth in Sri Lanka from 1981 to 2020. GDP per capita is used to measure economic growth, and net inflows (BoP, current million US dollars ) are used to measure FDI. To investigate the relationship between selected variables, unit root test, Johansen co-integration, Vector Error Correction Model (VECM) and Walt statistic test techniques were used. The finding indicates that there is no short or long-term relationship between the variables studied. However, favourable macroeconomic factors may aid economic growth. The implications of these findings emphasise the importance of the government and policymakers developing appropriate policies to improve the peaceful investment climate andfavourable macroeconomic factors.
Keywords: Foreign direct investment; Gross domestic product; Johansen co-integration; Unit root test; Vector error correction model